2022
DOI: 10.1002/jcsm.12941
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance training intensity on muscle quantity/quality in middle‐aged and older people: a randomized controlled trial

Abstract: Background A sarcopenia diagnosis is confirmed by the presence of low muscle quantity or quality under the 2018 revised definition by the European Working Group on Sarcopenia in Older People 2. Imaging methods [i.e. magnetic resonance imaging (MRI)], dual‐energy X‐ray absorptiometry (DXA), and bioelectrical impedance analysis are tools to evaluate muscle quantity or quality. The present study aimed to investigate whether and how low‐intensity and moderate‐intensity resistance training improved both muscle quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 37 publications
4
41
0
4
Order By: Relevance
“…Of note, the effects of QG supplementation on muscle quantity was observed only in whole-body lean mass on DXA, not in thigh muscle CSA on MRI (Supplementary Table 3). Our previous report showed that muscle CSAs on MRI would be more sensitive for detecting local muscle hypertrophy by resistance training than lean mass on DXA (10), which was confirmed in the present study; the changes in thigh muscle CSA (+5.6%) were higher than those of wholebody lean mass (+2.0%) by exercise alone during the 24-week intervention. In contrast, nutritional interventions may exert systemic effects on skeletal muscle, so that lean mass on DXA would be more appropriate for evaluating these effects.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Of note, the effects of QG supplementation on muscle quantity was observed only in whole-body lean mass on DXA, not in thigh muscle CSA on MRI (Supplementary Table 3). Our previous report showed that muscle CSAs on MRI would be more sensitive for detecting local muscle hypertrophy by resistance training than lean mass on DXA (10), which was confirmed in the present study; the changes in thigh muscle CSA (+5.6%) were higher than those of wholebody lean mass (+2.0%) by exercise alone during the 24-week intervention. In contrast, nutritional interventions may exert systemic effects on skeletal muscle, so that lean mass on DXA would be more appropriate for evaluating these effects.…”
Section: Discussionsupporting
confidence: 89%
“…A systematic review suggested a dose-response relationship between resistance training intensity and the increase in muscle mass in elderly people ( 9 ). Our previous study also showed that a higher intensity of resistance exercise was more effective for improving both muscle quantity and quality ( 10 ). In fact, we found that low-intensity, 40% 1-repetition maximum (1-RM) exercise for 24 weeks could improve muscle quantity, but not muscle quality, although both were improved by 60% 1-RM exercise for the same duration ( 10 ).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations